Can Andean potatoes be agronomically biofortified with iron and zinc fertilizers? - Kromann, P.; Valverde, F.; Alvarado, S.; Velez, R.; Pisuña, J.; Potosi, B.; Taipe, A.; Caballero, D.; Cabezas, A.; Devaux, A. (Springer, 2017)
The aim of this study was to investigate the proof-of-concept that Andean potato (Solanum tuberosum L., Andigenum Group) can be agronomically biofortified with iron (Fe) and zinc (Zn) fertilizers. Greenhouse and field experiments were conducted in the Ecuadorian Andes with varying rates of foliar and soil applied Fe and Zn fertilizers to investigate the potential resulting increase in tuber Fe and tuber Zn concentrations. The study showed that simple fertilizer practices enhancing Zn supply to potato plants can increase tuber Zn concentrations. The rate of increase of tuber Zn following Zn fertilization was similar across cultivars. A concomitant negative effect of high rates of Zn applications on yield was not seen, and a maximum Zn application level for increasing tuber Zn concentration was not identified. A positive tuber yield effect was seen at one field site. High rates of foliar Zn application reached a 2.51-fold tuber Zn increase, and high rates of soil Zn application a 1.91-fold tuber Zn increase. The experiments showed no positive correlation between Fe fertilization and Fe concentration in tubers. Moreover, the study showed a strong effect of site on the concentration of Fe and Zn in tubers, and the tuber mineral concentrations across sites and treatments were negatively correlated with tuber yield. The results confirmed the proof of concept that Andean potato cultivars can be agronomically Zn-biofortified with foliar and soil applied Zn fertilizers. Tuber Fe concentrations of Andean potatoes were not increased with Fe fertilization.